SISTEM POLITIK INDONESIA MENUJU â€œCIVIL SOCIETYâ€ (MASYARAKAT MADANI) - Sedarmayanti Sedarmayanti (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2004)
The political system in Indonesia has changed in line with the development of government model. Therefore, the patterns underlying the change of government closely influences the political system. Thus far, the political system of the country seems in quest of an ideal model by understanding and relating to the socio-political phenomena. The most difficult factor to find itÂ is the radical change of environment that may cause the incremental change of the structure. Apart ofÂ the various development, the goal of the political system seems to be the realization of civil society. To reach the goal, the first step to take is the implementation of good governance.